THE ECONOMIC FALLOUT OF THE US-CHINA TRADE WAR - Ilhomjonov, Ibrohim; Yakubov, Akbarali (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: The US-China trade war represents a significant disruption in global trade relations, prompting concerns about its economic repercussions. Specific Background: This study specifically investigates the relationship between escalating tariffs and GDP growth in both the United States and China, focusing on data from 2013 to 2022. Knowledge Gap: While prior research has explored various dimensions of the trade war, the direct quantitative impact of tariffs on GDP growth has not been thoroughly examined. Aims: This study aims to quantify the effects of increased tariffs on GDP growth in both countries using a robust multiple regression model. Results: The analysis reveals that a 1-unit increase in tariffs is associated with a decrease of 5.801 units in US GDP and a decrease of 5.188 units in China's GDP, indicating a detrimental impact on both economies. Notably, China demonstrates a higher sensitivity to tariff changes compared to the US. Novelty: By employing a rigorous quantitative approach, this research fills a crucial gap in the literature regarding the economic consequences of trade tensions. Implications: The findings underscore the necessity for cooperative trade policies and open markets to mitigate the adverse effects of tariffs and promote sustainable economic growth, highlighting the interdependence of the US and Chinese economies in an increasingly globalized landscape.